Pemanfaatan Aplikasi Akuntansi Sederhana dalam Meningkatkan Transparansi Keuangan Koperasi Desa - Edi Wahyudin; Fathurrohman; Agnes Rosmeri Manurung; Akdan Amrullah (CV. Multi Kreasi Media, 2022)
This Community Partnership Program aims to improve financial transparency and accountability in village cooperatives through the utilization of a simple accounting application. Activities include training on application usage, assistance in recording financial transactions, and evaluation of system implementation. It is expected that with this application, the financial management of cooperatives will become more structured, easily understandable, and accessible to members, thereby increasing trust and participation in cooperative activities.